A numerical study of input and output target instrumental measurement uncertainties for dimensional laser interferometry. (December 2021) - Martins, Luís Lages; Ribeiro, Álvaro Silva
Abstract: This study describes the development of a numerical tool, based on a Monte Carlo Method (MCM), aiming the determination of the target instrumental uncertainty of dimensional measurements with laser interferometry. The paper presents the adopted calculation procedure, namely, the mathematical models applied in the indirect determination of the refractive index of moist air, as well as the probabilistic formulation of the input quantities (laser wavelength in vacuum and environmental conditions). Simulations were performed for a wide range of observation conditions usually related to harsh environments (field measurements and industrial scenarios), showing a relative expanded (95%) target instrumental measurement uncertainty between 3, 1∙10 −7 and 3, 7∙10 −7 . A sensitivity analysis of the influence quantities revealed the atmospheric pressure target instrumental measurement uncertainty as the major contribution for the output dispersion of values.